Muscle synergy in several locomotor modes in chimpanzees and Japanese macaques, and its implications for the evolutionary origin of bipedalism through shared muscle synergies - Ryosuke Goto; Susan Larson; Tetsuya Shitara; Yu Hashiguchi; Yoshihiko Nakano (Scientific Reports)
Abstract Recent evidence indicates that human ancestors utilized a combination of quadrupedal walking, climbing, and bipedal walking. Therefore, the origin of bipedalism may be linked to underlying mechanisms supporting diverse locomotor modes. This study aimed to elucidate foundations of varied locomotor modes from the perspective of motor control by identifying muscle synergies and demonstrating similarities in synergy compositions across different locomotor modes in chimpanzees and Japanese macaques. Four muscle synergies were extracted for bipedal and quadrupedal walking in both the chimpanzees and macaques, as well as for vertical climbing in the chimpanzees. Bipedal walking synergies were generally analogous to those observed in quadrupedal walking and vertical climbing. Specifically, the bipedal walking synergies during the stance and swing phase in the chimpanzees were substitutable with those of vertical climbing and quadrupedal walking, respectively. For the macaque, not all bipedal walking synergies exhibited similarities to quadrupedal walking synergies, likely due to instability during the single support phase of bipedalism. These findings suggest that synergies from vertical climbing and quadrupedal walking might be transferred to bipedal walking, as seen in the chimpanzees, and that this sharing of synergies might form a foundation for a diverse range of locomotor capacities including bipedal walking.